The image of child protection social workers in the news and amongst children's professionals : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Manawatū, New Zealand - Harding, Simon James (Massey University, 2018)
This research examines portrayals of child protection social workers in New Zealand news reporting and explores how child protection social workers are perceived by their colleagues in the children’s workforce. The research set out not only to assess perceptions, but also to gain insight into how they are formed and to consider their implications. To this end, the research also examined children’s professionals’ perceptions of news coverage and sought to better understand the factors that influence professionals’ attitudes towards child protection social workers. Finally, professionals from the children’s workforce were asked how helpful they believed referrals to child protection social workers would be for a range of problems. The study is positioned within a critical realist outlook and uses mixed methodology. The data was sourced using two instruments. Firstly, professionals from the children’s workforce in New Zealand were invited to participate in an online survey. Secondly, two years of New Zealand news articles were analysed to assess how child protection social workers were portrayed. The principle findings of the research have been presented as they relate to five research questions. They underscore the importance of personal and professional relationships, and of academic and professional publications, in influencing children’s professionals’ perceptions of child protection social workers. They suggest children’s professionals tend to view child protection social workers somewhat favourably. On the other hand, news reporting was found to depict child protection social workers more negatively, although only marginally so. Children’s professionals appear to largely understand this. Alongside the more encouraging findings, negative perceptions of specific characteristics of child protection social workers were found to prevail in both news reporting and amongst children’s professionals. Perhaps of most concern, the findings identified a troubling lack of confidence in the potential helpfulness of referrals to child protection social workers. An analysis of these findings and themes from the literature indicates that the key perceptions of concern are unlikely to be divorced from substantive issues. Improving the image of child protection social workers in New Zealand will almost certainly require addressing some of the underlying causes of unfavourable perceptions.
Keywords: Mass media and social service|zNew Zealand; Social work with youth|zNew Zealand|xPublic opinion; Child welfare workers|zNew Zealand|xAttitudes; Child welfare workers|zNew Zealand|xPublic opinion